2016
DOI: 10.1002/chem.201600011
|View full text |Cite
|
Sign up to set email alerts
|

The Quadruple Bonding in C2 Reproduces the Properties of the Molecule

Abstract: Ever since Lewis depicted the triple bond for acetylene, triple bonding has been considered as the highest limit of multiple bonding for main elements. Here we show that C2 is bonded by a quadruple bond that can be distinctly characterized by valence-bond (VB) calculations. We demonstrate that the quadruply-bonded structure determines the key observables of the molecule, and accounts by itself for about 90% of the molecule's bond dissociation energy, and for its bond lengths and its force constant. The quadrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
94
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 102 publications
(153 reference statements)
16
94
0
3
Order By: Relevance
“…We wantt op oint out that the core of the controversy is not the number of bonds but the strengtho ft he total s bonding in C 2 ,w hich is suggestedb ys everalg roups to be much weaker than in acetylene. On page S23 of the Supporting Information [1] one finds as ketch of the two determinants Det1 and Det2 that describe the coupling between two carbon atomsi nt he 3 Ps tate (Det1) and the 5 Ss tate (Det2), which agreesw ith our descriptionso fY QC(1) and Y QC(2) in Figure 1. There are contradictings tatements and missingi nformation which make the numerical resulta nd the conclusion questionable.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…We wantt op oint out that the core of the controversy is not the number of bonds but the strengtho ft he total s bonding in C 2 ,w hich is suggestedb ys everalg roups to be much weaker than in acetylene. On page S23 of the Supporting Information [1] one finds as ketch of the two determinants Det1 and Det2 that describe the coupling between two carbon atomsi nt he 3 Ps tate (Det1) and the 5 Ss tate (Det2), which agreesw ith our descriptionso fY QC(1) and Y QC(2) in Figure 1. There are contradictings tatements and missingi nformation which make the numerical resulta nd the conclusion questionable.…”
supporting
confidence: 84%
“…

The title publication by Shaik et al [1] on the chemical bonding in C 2 is an important contributiont ou nderstand the origin of the conflicting views about the strengtho ft he interatomic interactions in dicarbon which are presented in their paper and in the publications of other groups using av ariety of methods. They calculate the in-situ strengtho ft he s bonding D 2s in-situ from the energyd ifference between Y 2s and Y QC .T his is shown in Figure 1w hich is adapted from Scheme 4o fS haik et al [1] Figure1as hows the quasiclassical state Y QC(1) that is depicted as Y QC in their Scheme 4. The results come from valence bond (VB) calculations, which give bond dissociation energies and bond lengths that are in good agreement with experimental data and with the results of the other methods.

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11] According to Shaik et al, [1][2][3][4] in its X 1 † C g ground state C 2 features a quadruple bond comprised of two bonds and two bonds. However, despite its higher multiplicity, this quadruple bond is weaker than the triple carbon-carbon bond in ground-state ethyne, C 2 H 2 , which has a higher force constant and a shorter bond length.…”
Section: Introductionmentioning
confidence: 99%
“…The description of bonding in small molecules remains a challenge: although for simple diatomic molecules chemical bonding seems clear, the situation in C 2 showed that it can still lead to surprises [1][2][3][4][5][6][7]. Several theoretical studies, at various levels of theory, have been devoted to describe the chemical bonding in the C 2 molecule.…”
Section: Introductionmentioning
confidence: 99%